Digital solidarity and adaptation: applications developed for refugees in host countries - Özdemir, Özlem; Görgün, Melih; Sarıoğlu, Elif Başak (Frontiers in Sociology, 2024)
The scale of international migration is growing day by day, and the issue of refugees constitutes a significant agenda item for all countries. In today's digital age, characterized by technological advancements, refugees are also benefiting from the advantages of technology. With various applications downloaded to their mobile phones, refugees can directly access all kinds of information about the countries they are heading to and even communicate with each other to share experiences. This study explores how mobile phone applications can be developed to serve the refugees in the familiarizing themselves with the receiving culture. In the study, a total of 10 applications prepared for refugees on Android and iOS platforms, selected by random sampling and purposeful sampling methods, were examined. These applications were analyzed using the qualitative content analysis method. As a result, when the applications developed in host countries were examined, it was observed that the most needed basic information for refugees, such as housing, education, finding a job, health, language, daily words, legal documents, rules, and fundamental rights, was provided. Additionally, in the 10 refugee applications examined, Global Positioning System (GPS) and Geographic Information System (GIS) were used as locative media for mapping locations. Location-based data and maps that show where refugees are located are extremely important for them. These maps are believed to help reduce stress, make them feel safe, and facilitate the adaptation process by showing refugees the nearest shelters, dining places, hospitals, transportation, and asylum locations.